Silicon carbide coating material and method for producing the same

CN118495996BActive Publication Date: 2026-10-13湖南德智新材料股份有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410544329.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2026-10-13
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

[0002]化学气相沉积法(CVD)制备的石墨基碳化硅涂层在外延过程中经常发生涂层脱落的问题,可能的原因主要有两方面:一方面是由于碳化硅涂层和石墨基底热膨胀系数的不匹配,不可避免地产生制备温度冷却时形成的贯穿涂层的微裂纹,以及基底与涂层的界面应力较大,进而引发碳化硅涂层脱落;另一方面则是由于CVD法直接在石墨基底上沉积碳化硅涂层,由于沉积速率较快,容易在石墨界面出现空洞等缺陷,导致涂层不连续,这将成为裂纹起始点,为碳化硅涂层脱落埋下隐患

Benefits of technology

[0011](1)本发明提供的碳化硅涂层材料,具有梯度分布的碳化硅内涂层,形成梯度界面,减少碳化硅与石墨的界面缺陷,降低涂层开裂和脱落的风险,提高碳化硅涂层的稳定性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of semiconductor materials, and provides a silicon carbide material and a preparation method thereof. The silicon carbide coating material comprises a carbon base and a silicon carbide composite coating arranged on the surface of the carbon base, the silicon carbide composite coating comprises at least two layers of silicon carbide inner coatings with different silicon contents and at least one layer of a silicon carbide outer coating with basically unchanged silicon content; in the silicon carbide composite coating, the silicon content of the silicon carbide inner coating gradually increases along the growth direction of the silicon carbide inner coating; the C / Si molar ratio in the silicon carbide inner coating is 1:(0.4-1.1); and the C / Si molar ratio in the silicon carbide outer coating is 1:(0.9-1.1). The silicon carbide coating material has the silicon carbide inner coating with gradient distribution, forms a gradient interface, reduces the interface defects of the silicon carbide coating and the graphite, reduces the risk of cracking and falling of the coating, and improves the stability of the silicon carbide coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of semiconductor materials, specifically to a silicon carbide material and its preparation method. Background Technology

[0002] Graphite-based silicon carbide coatings prepared by chemical vapor deposition (CVD) often experience coating detachment during epitaxy. The main reasons are twofold: First, the mismatch in thermal expansion coefficients between the silicon carbide coating and the graphite substrate inevitably leads to microcracks penetrating the coating during cooling, as well as high interfacial stress between the substrate and coating, thus causing coating detachment. Second, the direct deposition of silicon carbide coatings on the graphite substrate using CVD, due to its rapid deposition rate, easily results in defects such as voids at the graphite interface, causing coating discontinuity. This becomes a crack initiation point, creating a potential hazard for silicon carbide coating detachment.

[0003] Therefore, it is of great significance to develop a silicon carbide coating material whose coating is not easy to peel off. Summary of the Invention

[0004] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a silicon carbide material and its preparation method. This silicon carbide coating material has a gradient-distributed silicon carbide inner coating, forming a gradient interface, reducing interface defects between silicon carbide and graphite, lowering the risk of coating cracking and peeling, and improving the stability of the silicon carbide coating.

[0005] To achieve the above objectives, a first aspect of the present invention provides a silicon carbide coating material, the silicon carbide coating material comprising a carbon substrate and a silicon carbide composite coating disposed on the surface of the carbon substrate, the silicon carbide composite coating comprising at least two silicon carbide inner coatings with different silicon contents and at least one silicon carbide outer coating with substantially constant silicon content; in the silicon carbide composite coating, the silicon content of the silicon carbide inner coating gradually increases along the growth direction of the silicon carbide inner coating; the C / Si molar ratio in the silicon carbide inner coating is 1:(0.4-1.1); and the C / Si molar ratio in the silicon carbide outer coating is 1:(0.9-1.1).

[0006] A second aspect of the present invention provides a method for preparing the silicon carbide coating material described in the first aspect of the present invention, comprising the following steps:

[0007] (1) Substrate pretreatment: The substrate is immersed in a flowing solution for sandblasting and drying;

[0008] (2) Preparation of silicon carbide inner coating by embedding method: The pretreated substrate is embedded in a mixture of carbon powder and silicon powder, heated to 1800-2200℃, kept at the temperature for 1-3h, and the mass ratio of carbon powder and silicon powder is adjusted to obtain a multilayer silicon carbide inner coating with a gradient distribution of silicon content.

[0009] (3) CVD deposition of silicon carbide outer coating: The product obtained in step (2) is placed in a chemical vapor deposition equipment, and a mixture of silicon carbide source gas, carrier gas and dilution gas is introduced. The deposition temperature is 1200℃-1600℃, the deposition pressure is 7000Pa-15000Pa, and the deposition time is 5h-15h.

[0010] The present invention, by adopting the above technical solution, has the following beneficial effects:

[0011] (1) The silicon carbide coating material provided by the present invention has a gradient distribution of silicon carbide inner coating to form a gradient interface, reduce interface defects between silicon carbide and graphite, reduce the risk of coating cracking and peeling, and improve the stability of silicon carbide coating.

[0012] (2) The silicon carbide coating material provided by the present invention has a small difference in the coefficient of thermal expansion between the gradient-distributed silicon carbide inner coating and the carbon substrate, which increases the bonding ability between the substrate and the coating.

[0013] (3) The method for preparing silicon carbide coating material provided by the present invention uses a combination of embedding method and CVD method to prepare silicon carbide composite coating, which can improve the bonding force between silicon carbide composite coating and substrate, reduce the risk of coating cracking and peeling, and improve the external density of silicon carbide composite coating, thus effectively improving the stability of silicon carbide composite coating.

[0014] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to those ranges or values. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In this document, unless otherwise specified, data ranges include endpoints. Detailed Implementation

[0015] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0016] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0017] The first aspect of the present invention provides a silicon carbide coating material, the silicon carbide coating material comprising a carbon substrate and a silicon carbide composite coating disposed on the surface of the carbon substrate, the silicon carbide composite coating comprising at least two silicon carbide inner coatings with different silicon contents and at least one silicon carbide outer coating with substantially constant silicon content; in the silicon carbide composite coating, the silicon content of the silicon carbide inner coating gradually increases along the growth direction of the silicon carbide inner coating; the C / Si molar ratio in the silicon carbide inner coating is 1:(0.4-1.1); the C / Si molar ratio in the silicon carbide outer coating is 1:(0.9-1.1).

[0018] The silicon carbide coating material of the present invention has a Si element content that gradually increases along the growth direction of the silicon carbide inner coating, thereby achieving a gradient distribution of Si elements from the substrate to the coating, forming a gradient interface. This reduces interface defects between silicon carbide and graphite, decreases the probability of coating peeling caused by interface stress concentration, reduces the risk of coating cracking and peeling, and improves the stability of the silicon carbide coating.

[0019] Furthermore, the Si content in the silicon carbide inner coating gradually increases along the growth direction of the silicon carbide inner coating, so that the Si content in the silicon carbide inner coating is the same as or slightly different from the Si content in the silicon carbide outer coating. At this time, the Si content is smaller and the C content is larger at the end of the silicon carbide inner coating closer to the carbon substrate, so that the thermal expansion coefficients of the silicon carbide inner coating and the carbon substrate are less different, and the bonding force is stronger.

[0020] In some embodiments, the silicon carbide composite coating includes at least two silicon carbide inner coatings with different silicon contents, and the silicon content gradually increases along the growth direction of the silicon carbide inner coatings. For example, the silicon carbide composite coating includes three, four, five or more layers. The number of inner coating layers can be adjusted according to actual needs, ensuring at least two inner coating layers to form a gradient interface, reduce interface stress, and reduce the risk of coating cracking and detachment.

[0021] The more layers of silicon carbide inner coating, the smaller the difference in C element content between each silicon carbide inner coating, and the smaller the difference in thermal expansion coefficient between the carbon substrate and the silicon carbide composite coating, which is more conducive to improving the bonding force between the silicon carbide composite coating and the carbon substrate.

[0022] In some embodiments, the silicon carbide inner coating includes a first silicon carbide inner coating, a second silicon carbide inner coating, and a third silicon carbide inner coating. Considering the advantages of multilayer inner coatings and the simplicity of the processing technology, it is preferable to have a three-layer silicon carbide inner coating. This ensures that the silicon carbide inner coating forms a good gradient interface, improves the adhesion between the silicon carbide composite coating and the carbon substrate, reduces the risk of coating cracking and delamination, and simplifies the preparation process.

[0023] In some embodiments, the C / Si molar ratio in the first silicon carbide inner coating is 1:(0.4-0.6), for example, it can be 1:0.4, 1:0.42, 1:0.44, 1:0.45, 1:0.48, 1:0.5, 1:0.52, 1:0.54, 1:0.55, 1:0.58, or 1:0.6.

[0024] In some embodiments, the C / Si molar ratio in the second silicon carbide inner coating is 1:(0.6-0.8), for example, it can be 1:0.6, 1:0.62, 1:0.64, 1:0.65, 1:0.68, 1:0.7, 1:0.72, 1:0.74, 1:0.75, 1:0.78, or 1:0.8.

[0025] In some embodiments, the C / Si molar ratio in the second silicon carbide inner coating is 1:(0.9-1.1), for example, it can be 1:0.9, 1:0.92, 1:0.94, 1:0.95, 1:0.98, 1:1.0, 1:1.02, 1:1.04, 1:1.05, 1:1.08, or 1:1.1.

[0026] When three inner coating layers are applied, the C / Si molar ratio of each inner coating layer is controlled within the above range, which can better improve the adhesion between the silicon carbide composite coating and the carbon substrate and reduce the risk of coating cracking and detachment.

[0027] In some embodiments, the thickness of the first silicon carbide inner coating is 10-30 μm, for example, it can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, or 30 μm.

[0028] In some embodiments, the thickness of the second silicon carbide inner coating is 10-30 μm, for example, it can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, or 30 μm.

[0029] In some embodiments, the thickness of the third silicon carbide inner coating is 10-30 μm, for example, it can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, or 30 μm.

[0030] When setting a three-layer inner coating, it is necessary to consider not only the C / Si molar ratio of each silicon carbide inner coating layer, but also the thickness range of each silicon carbide inner coating layer. When the thickness of the three silicon carbide inner coating layers is set within the above range, this invention can avoid the overall thickness of the inner coating layer being too high due to excessive thickness of each inner coating layer, which increases the heat conduction path and leads to a decrease in heat conduction performance, affecting the thermal conductivity and stability of the carbon substrate in high-temperature environments. It can also avoid the situation where the thickness of each inner coating layer is too low, which cannot form an effective interface gradient and is not conducive to reducing the risk of coating cracking and delamination.

[0031] In some embodiments, the total thickness of the silicon carbide inner coating is 30 μm-60 μm.

[0032] In some embodiments, the C / Si molar ratio in the silicon carbide outer coating is 1:(0.9-1.1), for example, it can be 1:0.9, 1:0.92, 1:0.95, 1:0.98, 1:1, 1:1.02, 1:1.05, 1:1.08, 1.1, preferably 1:1.

[0033] In some embodiments, the thickness of the silicon carbide outer coating is 30μm-60μm, for example, it can be 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, or 60μm.

[0034] Maintaining a C / Si molar ratio of approximately 1:1 in the silicon carbide outer coating and limiting the thickness of the silicon carbide outer coating within the aforementioned range ensures that the silicon carbide composite coating exhibits excellent high-temperature resistance, corrosion resistance, mechanical properties, and thermal conductivity.

[0035] In some embodiments, the carbon substrate includes graphite, C f / C、C f / SiC、SiC f At least one of C. Carbon substrate is preferred over graphite substrate. Graphite substrate, as a reactor material, can withstand high temperatures and chemical corrosion and has low chemical reactivity.

[0036] In some embodiments, the surface roughness of the carbon substrate is 1.5 μm-5 μm. This invention uses a carbon substrate with higher roughness; the rough surface has more microscopic irregularities and structures, which can increase the contact area between the coating and the substrate, improve the adhesion between the silicon carbide composite coating and the carbon substrate, and reduce the risk of coating cracking and detachment.

[0037] In some embodiments, the coefficient of thermal expansion of the carbon substrate is (4.0-5.2)×10⁻⁶. -6 / K. The silicon carbide composite coating of the present invention can be applied to carbon substrates with a large range of fluctuating coefficients of thermal expansion, such as graphite, whose coefficient of thermal expansion is generally 4.5 × 10⁻⁶.-6 The temperature is above / K and unstable, with even greater differences at high temperatures of 1200℃. However, after the silicon carbide composite coating of the present invention is applied to the graphite substrate, the bonding force between the silicon carbide composite coating and the graphite substrate can still be improved, reducing the risk of coating cracking and detachment.

[0038] A second aspect of the present invention provides a method for preparing the silicon carbide coating material described in the first aspect of the present invention, comprising the following steps:

[0039] (1) Substrate pretreatment: The substrate is immersed in a flowing solution for sandblasting and drying;

[0040] (2) Preparation of silicon carbide inner coating by embedding method: The pretreated substrate is embedded in a mixture of carbon powder and silicon powder, heated to 1800-2200℃, kept at the temperature for 1-3h, and the mass ratio of carbon powder and silicon powder is adjusted to obtain a multilayer silicon carbide inner coating with a gradient distribution of silicon content.

[0041] (3) CVD deposition of silicon carbide outer coating: The product obtained in step (2) is placed in a chemical vapor deposition equipment, and a mixture of silicon carbide source gas, carrier gas and dilution gas is introduced. The deposition temperature is 1200℃-1600℃, the deposition pressure is 7000Pa-15000Pa, and the deposition time is 5h-15h.

[0042] <Substrate Pretreatment>

[0043] In the existing technology, although there is also a graphite substrate sandblasting operation to increase the roughness of the graphite substrate, conventional sandblasting directly uses sandblasting equipment to spray abrasive onto the graphite surface (the graphite is not immersed in the solution). The abrasive polishes the graphite surface to increase the roughness and increase the mechanical adhesion between the coating and the graphite.

[0044] However, this invention has found that during the conventional sandblasting process, pits or defects are sometimes formed on the graphite surface. If the abrasive has a low mesh size, it is very likely that the abrasive will be embedded in the pit and cannot be effectively cleaned. The silicon carbide abrasive remaining in the pit can easily become the starting point of cracks, causing the silicon carbide coating to crack and peel off.

[0045] In conventional sandblasting processes, high-speed abrasive particles generate intense impact and friction on the surface, leading to a rapid increase and subsequent decrease in surface temperature. This drastic temperature change causes residual thermal stress within the material, which in turn leads to microcracks between the graphite and the coating, weakening the interfacial bond. This invention immerses the substrate in a flowing solution for sandblasting. The flowing solution removes residual silicon carbide abrasive particles left during sandblasting, reducing the presence of residual particles and lowering the risk of cracking and peeling of the silicon carbide coating; it also reduces concentrated thermal stress.

[0046] In some embodiments, the solution can be water, salt solution, alcohol solution, etc., with water being preferred due to its low cost and lack of pollution.

[0047] In some embodiments, the process parameters for substrate pretreatment include: a solution flow rate of 2 L / min-10 L / min, a solution overflow of 2 mm-10 mm above the substrate surface, a nozzle distance of 8 cm-12 cm from the substrate surface, and a blasting pressure of 2-5 kg / cm². 2 The nozzle tilt angle is 40° to 60°.

[0048] In some embodiments, the solution flow rate can be 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, or 10 L / min.

[0049] In some embodiments, the solution extends beyond the upper surface of the substrate by 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm.

[0050] In some embodiments, the nozzle is 8cm, 9cm, 10cm, 11cm, or 12cm away from the upper surface of the substrate.

[0051] In some implementations, the sandblasting pressure is 2 kg / cm². 2 3kg / cm 2 4kg / cm 2 5kg / cm 2 .

[0052] In some embodiments, the nozzle tilt angle is 40°, 45°, 48°, 50°, 55°, or 60°.

[0053] When the solution flow rate is limited to the above range, residual sand can be effectively removed while minimizing its impact on the sandblasting effect. When the distance of the solution beyond the substrate surface is limited to the above range, the flowing solution can fully wet the upper surface of the graphite, allowing the flowing solution to better carry away residual sand and reducing the likelihood of residual sand remaining in pits. When the distance between the nozzle and the substrate surface and the sandblasting pressure are limited to the above range, the impact force and coverage area of ​​the sand particles on the substrate surface can be affected, resulting in a substrate with a suitable roughness. When the nozzle tilt angle is limited to the above range, the sprayed sand particles can cover the substrate surface more evenly, helping to ensure that the entire surface receives a uniform impact, thereby improving the uniformity and consistency of the processing.

[0054] In some embodiments, the blasting material is selected from at least one of silica sand, glass beads, steel grit, and corundum. Silica sand, such as fine silicon carbide sand, is preferred.

[0055] In some embodiments, the grit number of the sandblasting material is 100-300 mesh.

[0056] <Preparation of silicon carbide inner coating by embedding method>

[0057] Firstly, a multi-layer silicon carbide inner coating is prepared on the graphite surface by the embedding method, which not only requires simple equipment and low cost, but also allows the silicon carbide inner coating to fully spread on the surface of the base material, seal defects such as holes on the surface of the base material, and the coating has good continuity, and is not prone to cracking and peeling off.

[0058] In some embodiments, when the silicon carbide inner coating is prepared by the embedding method, the temperature is 1800-2200°C, and the time is 1-3h. The temperature and time for preparing different silicon carbide inner coatings can be adjusted within the above range according to actual conditions.

[0059] In some embodiments, the silicon carbide inner coating includes a first silicon carbide inner coating, a second silicon carbide inner coating, and a third silicon carbide inner coating. Providing three layers of silicon carbide inner coating can ensure the formation of a gradient interface in the silicon carbide inner coating, improve the bonding force between the silicon carbide composite coating and the carbon substrate, and reduce the risk of coating cracking and peeling off.

[0060] In some embodiments, when preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(0.93-1.4), for example, it can be 1:0.93, 1:0.95, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4.

[0061] In some embodiments, when preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(1.4-1.87), for example, it can be 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.85, 1:1.87;

[0062] In some embodiments, when preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(2.1-2.57). For example, it can be 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.55, 1:2.57.

[0063] When preparing different silicon carbide inner coatings, the steps of the embedding method are repeated, and the mass ratio of carbon powder to silicon powder is adjusted within different ranges each time, so as to obtain silicon carbide inner coatings with different C / Si molar ratios.

[0064] <CVD deposition of silicon carbide outer coating>

[0065] In some embodiments, the deposition temperature of the CVD deposition of the silicon carbide outer coating is 1200℃-1600℃, for example, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃. When the deposition temperature is within the above range, it can promote the growth of silicon carbide crystals, resulting in smaller grain size and a denser silicon carbide coating structure.

[0066] In some embodiments, the deposition pressure is 7000 Pa to 15000 Pa, for example, 7000 Pa, 8000 Pa, 10000 Pa, 12000 Pa, 14000 Pa, or 15000 Pa. When the deposition pressure is within the above range, the deposition rate can be avoided, reducing the risk of void defects in the SiC outer coating.

[0067] In some implementations, the deposition time is 5-15 hours. The deposition time is not strictly limited and can be adjusted according to the thickness of the SiC outer coating.

[0068] In some embodiments, the silicon-carbon source gas is selected from at least one of trichloromethylsilane, trichlorosilane, and tetrachlorosilane, or other silicon-carbon source gases suitable for preparing SiC coatings in the art.

[0069] In some embodiments, the carrier gas is selected from hydrogen.

[0070] In some embodiments, the diluent gas is selected from at least one of argon, nitrogen, and helium.

[0071] In some embodiments, the flow rate ratio of the silicon-carbon source gas to the carrier gas is 1:(4-20), for example, 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, or 1:20. When the flow rate ratio of the silicon-carbon source gas to the carrier gas is within the above range, a silicon carbide outer coating with smaller SiC grain size can be obtained, increasing the density of the silicon carbide outer coating and improving the high-temperature resistance, corrosion resistance, mechanical properties, and thermal conductivity of the silicon carbide composite coating.

[0072] In some embodiments, the flow rate of the silicon-carbon source gas is 30 g / min to 180 g / min.

[0073] In some embodiments, the flow rate of the carrier gas is 50 L / min to 150 L / min.

[0074] The formula for converting the unit of carbon-silicon source gas to L / min is V = a * Vm / M, where a represents the mass of MTS (g), M represents the molar mass of MTS: 149.5 g / mol, and Vm represents the molar volume of MTS (22.4 L / mol). For example, if the flow rate of MTS is 60 g / min and the flow rate of H2 is 0 L / min, converting the MTS volume to volume, 60 × 22.4 / 149.5 ≈ 9 L / min. Therefore, the flow rate ratio of MTS to H2 is approximately 9:100 ≈ 1:11.

[0075] In some embodiments, the flow rate of the diluent gas is 30 L / min to 120 L / min.

[0076] This invention employs a combination of embedding and CVD methods to prepare multilayer silicon carbide coatings, forming silicon carbide composite coatings. On one hand, the embedding method for preparing multilayer gradient silicon carbide inner coatings can improve the adhesion between the silicon carbide composite coating and the substrate, reducing the risk of cracking and peeling of the silicon carbide composite coating. On the other hand, the CVD method is used to prepare an outer silicon carbide coating, which improves the external density of the silicon carbide composite coating and can effectively improve the stability of the silicon carbide composite coating.

[0077] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0078] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.

[0079] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.

[0080] Example 1

[0081] A method for preparing a silicon carbide coating material includes the following steps:

[0082] (1) Pretreatment of graphite substrate: The graphite substrate was placed in an aqueous solution, with the aqueous solution exceeding the upper surface of the graphite by 5 mm. The flow rate of the aqueous solution was approximately 8 L / min. Then, the surface of the graphite substrate was subjected to underwater sandblasting using a sandblasting machine with an inlet pressure of 8 kg / cm². 2 The sandblasting pressure is 3 kg / cm. 2 The silicon carbide sand has a mesh size of 200 and is blasted at an angle of about 45° onto the graphite surface. The nozzle is 10cm away from the graphite surface. After blasting, the surface roughness of the graphite is about 3.0μm. Then the graphite is cleaned and dried.

[0083] (2) Preparation of silicon carbide internal coating by embedding method: A pretreated graphite substrate is placed in a graphite crucible and embedded in powder, namely silicon powder and carbon powder. The particle size of the silicon powder is between 0.5 μm and 5 μm, and the particle size of the carbon powder is between 1 μm and 10 μm. The graphite crucible is placed in a vertical vacuum furnace with graphite as the heating element. The furnace temperature is raised from room temperature to about 2000℃ and held for about 2 hours to obtain the silicon carbide internal coating.

[0084] In the preparation of the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:0.93-1.4, the molar ratio of C / Si is 1:0.4-0.6, and the thickness is 10-30 μm.

[0085] When preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:1.4-1.87, the C / Si molar ratio is 1:0.6-0.8, and the thickness is 10-30 μm;

[0086] When preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:2.1-2.57, the C / Si molar ratio is 1:0.9-1.1, and the thickness is 10-30 μm;

[0087] (3) CVD deposition of silicon carbide outer coating: The product obtained in step (2) is placed in a CVD deposition furnace at a temperature of about 1400℃ and a pressure of about 10000Pa. 60g / min of MTS (trichloromethylsilane), 100L / min of H2 and 100L / min of Ar are introduced. The flow ratio of MTS to H2 is 1:11. Deposition is carried out for 10h, and the C / Si molar ratio is 1:1 with a thickness of about 45μm.

[0088] Example 2 group

[0089] This set of examples illustrates the effect of changing the number of silicon carbide inner coating layers on the properties of silicon carbide coating materials.

[0090] Example 2a: The method of Example 1 is followed, except that only the first silicon carbide inner coating and the second silicon carbide inner coating are prepared in step (2), that is, only two layers of inner coating are set.

[0091] Example 2b: The operation is carried out in accordance with the method of Example 1, except that a fourth silicon carbide inner coating is also prepared in step (2), that is, the inner coating is set with four layers. When preparing the fourth silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:2.3-2.8, the molar ratio of C / Si is 1:1.0-1.2, and the thickness is 10-20μm.

[0092] Example 3 Group

[0093] This set of examples illustrates the effect of changing the C / Si molar ratio in the silicon carbide inner coating on the properties of the silicon carbide coating material.

[0094] Example 3a: The procedure was performed in accordance with the method of Example 1, except that when preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:0.93 and the C / Si molar ratio was 1:0.4; when preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.4 and the C / Si molar ratio was 1:0.6; and when preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:2.1 and the C / Si molar ratio was 1:0.9.

[0095] Example 3b: The procedure was performed according to Example 1, except that in preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.4, and the C / Si molar ratio was 1:0.6; in preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.87, and the C / Si molar ratio was 1:0.8; and in preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:2.57, and the C / Si molar ratio was 1:1.1.

[0096] Example 3c: The method of Example 1 was followed, except that when preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:0.7 and the C / Si molar ratio was 1:0.3; when preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.17 and the C / Si molar ratio was 1:0.5; and when preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.87 and the C / Si molar ratio was 1:0.8.

[0097] Example 3d: The procedure was performed in accordance with the method of Example 1, except that when preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:1.63 and the C / Si molar ratio was 1:0.7; when preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:2.1 and the C / Si molar ratio was 1:0.9; and when preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder was 1:2.8 and the C / Si molar ratio was 1:1.2.

[0098] Example 4 group

[0099] This set of examples illustrates the effect of changes in the thickness of the silicon carbide inner coating on the properties of the silicon carbide coating material.

[0100] Example 4a: The method of Example 1 is followed, except that the thickness of the first silicon carbide inner coating is 10 μm, the thickness of the second silicon carbide inner coating is 10 μm, and the thickness of the third silicon carbide inner coating is 10 μm.

[0101] Example 4b: The method of Example 1 is followed, except that the thickness of the first silicon carbide inner coating is 30 μm, the thickness of the second silicon carbide inner coating is 30 μm, and the thickness of the third silicon carbide inner coating is 30 μm.

[0102] Example 4c: The method of Example 1 is followed, except that the thickness of the first silicon carbide inner coating is 7 μm, the thickness of the second silicon carbide inner coating is 7 μm, and the thickness of the third silicon carbide inner coating is 7 μm.

[0103] Example 4d: The method of Example 1 was followed, except that the thickness of the first silicon carbide inner coating was 35 μm, the thickness of the second silicon carbide inner coating was 35 μm, and the thickness of the third silicon carbide inner coating was 35 μm.

[0104] Example 5 group

[0105] This set of examples illustrates the effect of changes in graphite substrate pretreatment conditions on the properties of silicon carbide coating materials.

[0106] Example 5a: The procedure was performed according to Example 1, except that the aqueous solution exceeded the upper surface of the graphite by 2 mm, the flow rate of the aqueous solution was 2 L / min, and the sandblasting pressure was 2 kg / cm². 2 The nozzle tilt angle is 60°, and the surface roughness of the graphite after sandblasting is 1.9μm.

[0107] Example 5b: The procedure was performed according to Example 1, except that the aqueous solution exceeded the upper surface of the graphite by 10 mm, the flow rate of the aqueous solution was 10 L / min, and the sandblasting pressure was 5 kg / cm². 2 The nozzle tilt angle is 40°, and the surface roughness of the graphite after sandblasting is 1.7μm.

[0108] Example 5c: The method of Example 1 was followed, except that the solution exceeded the upper surface of the graphite by 15 mm, the flow rate of the aqueous solution was 15 L / min, and the surface roughness of the graphite after sandblasting was 1.4 μm.

[0109] Example 5d: The method of Example 1 was followed, except that the solution exceeded the upper surface of the graphite by 0.5 mm, the flow rate of the aqueous solution was 1 L / min, and the surface roughness of the graphite after sandblasting was 2.5 μm.

[0110] Example 6 group

[0111] This set of examples illustrates the impact of changes in silicon carbide external coating process conditions on the properties of silicon carbide coating materials.

[0112] Example 6a: The method described in Example 1 was followed, except that 33 g / min of MTS (trichloromethylsilane) and 100 L / min of H2 were introduced, with an MTS to H2 flow rate ratio of 1:20.

[0113] Example 6b: The method described in Example 1 was followed, except that 167 g / min of MTS (trichloromethylsilane) and 100 L / min of H2 were introduced, with an MTS to H2 flow rate ratio of 1:4.

[0114] Comparative Example 1

[0115] The method described in Example 1 is followed, except that in step (2), only the first silicon carbide inner coating is prepared, that is, only one inner coating layer is provided.

[0116] Comparative Example 2

[0117] The method described in Example 1 is followed, except that step (3) is omitted and only a silicon carbide inner coating is applied.

[0118] Comparative Example 3

[0119] The method described in Example 1 is followed, except that step (2) is omitted and only a silicon carbide outer coating is applied.

[0120] Comparative Example 4

[0121] The method described in Example 1 is followed, except that the graphite substrate is not pretreated, i.e., it is not subjected to underwater sandblasting.

[0122] Comparative Example 5

[0123] The method described in Example 1 is followed, except that the graphite substrate is subjected to conventional sandblasting treatment, i.e., the graphite substrate is not immersed in water.

[0124] The silicon carbide composite materials obtained in the above embodiments and comparative examples were subjected to the following tests:

[0125] (1) Substrate roughness test

[0126] The surface roughness of graphite was tested using a surface roughness tester (surface profilometer). The sample was fixed on a stable and vibration-free worktable. The parameters of the profilometer, such as the number of data points to be collected, the scanning length, and the rate, were set. The device was started and the probe was brought into contact with the object under test. The probe was controlled to move along a predetermined path, and the changes in the output signal of the displacement sensor caused by the undulations of the material surface were recorded. The data was received by the displacement sensor, amplified, and converted into electrical signal data. The software calculated various roughness parameters, and Ra (arithmetic mean deviation) was used to represent the measured roughness. The roughness of a single sample was tested at four points on the outer ring and three points on the inner ring. The average value of the seven points was used to represent the actual roughness of the sample. The test results are recorded in Table 1.

[0127] (2) Combined strength test

[0128] Referring to GB / T 31541-2015 standard "Test Method for Tensile and Shear Bond Strength of Fine Ceramic Interfaces - Cross-Cross Method", a universal testing machine was used to determine the bonding strength of the interface between the substrate and the coating, including the following steps:

[0129] Measure the width and thickness of the sample, and place the sample on a fixture with a span of 4 mm; open the software and connect it online, select the test method as bending strength, and set the speed to 0.5 mm / min; input the width and thickness of the sample, and reset the force, displacement, time, and speed to zero, then click start; combine with the strength calculation formula: Where: Rm—bond strength; FM—maximum load; A—cross-sectional area. The test results are recorded in Table 1.

[0130] (3) Thermal shock performance test

[0131] The silicon carbide product was kept at 400℃ for 15 minutes and then cooled by air. This test was repeated multiple times until cracks appeared on the surface of the silicon carbide product. The number of cycles was recorded as the number of thermal shock failures. The thermal shock performance of the product was evaluated by the number of thermal shock failures. The higher the number of thermal shock failures, the better the thermal shock performance and the lower the risk of coating cracking and peeling. The test results are recorded in Table 1.

[0132] Table 1

[0133] Example 1 1.8 25 100 Example 2a 1.8 24.1 93 Example 2b 1.8 24.2 96 Example 3a 1.8 24.5 97 Example 3b 1.8 23.8 98 Example 3c 1.8 22.3 91 Example 3d 1.8 21.6 90 Example 4a 1.8 24.6 96 Example 4b 1.8 24.5 95 Example 4c 1.8 21.8 89 Example 4d 1.8 21.1 88 Example 5a 1.9 23.9 95 Example 5b 1.7 23.5 94 Example 5c 1.4 20.6 86 Example 5d 2.5 21.3 87 Example 6a 1.8 24.6 98 Example 6b 1.8 24.4 94 Comparative Example 1 1.8 20 81 Comparative Example 2 1.8 18 76 Comparative Example 3 1.8 21 83 Comparative Example 4 0.9 15 70 Comparative Example 5 1.5 19 78

[0134] As shown in Table 1, compared with Comparative Examples 1-5, the coating of Example 1 exhibits the best adhesion and thermal shock resistance. This indicates that products with no pretreatment or underwater sandblasting of the graphite substrate, and coatings consisting of only a single inner or outer layer, have poorer coating adhesion and thermal shock resistance. Comparing Examples 2-6, the number of inner coating layers has the greatest impact on coating adhesion and thermal shock resistance, followed by the C / Si molar ratio, then the graphite substrate pretreatment conditions, then the flow ratio of trichloromethylsilane to carrier gas, and finally the inner coating thickness.

[0135] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications or equivalent substitutions made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a silicon carbide coating material, characterized in that, Includes the following steps: (1) Substrate pretreatment: The substrate is immersed in a flowing solution for sandblasting and drying; The process parameters for substrate pretreatment include: solution flow rate of 2-10 L / min, solution exceeding the substrate surface by 2-10 mm, nozzle distance from the substrate surface of 8-12 cm, and blasting pressure of 2-5 kg / cm². 2 The nozzle tilt angle is 40°-60°; (2) Preparation of silicon carbide inner coating by embedding method: The pretreated substrate is embedded in a mixture of carbon powder and silicon powder, heated to 1800-2200℃, kept at the temperature for 1-3h, and the mass ratio of carbon powder and silicon powder is adjusted to obtain a multilayer silicon carbide inner coating with a gradient distribution of silicon content. (3) CVD deposition of silicon carbide outer coating: The product obtained in step (2) is placed in a chemical vapor deposition equipment, and a mixture of silicon carbide source gas, carrier gas and dilution gas is introduced. The deposition temperature is 1200℃-1600℃, the deposition pressure is 7000Pa-15000Pa, and the deposition time is 5h-15h. The silicon carbide inner coating includes a first silicon carbide inner coating, a second silicon carbide inner coating, and a third silicon carbide inner coating; When preparing the first silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(0.93-1.4); When preparing the second silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(1.4-1.87); When preparing the third silicon carbide inner coating, the mass ratio of carbon powder to silicon powder is 1:(2.1-2.57); The particle size of the toner is 1μm-10μm, and the particle size of the silicon powder is 0.5μm-5μm.

2. The method according to claim 1, characterized in that, In step (1), the blasting material is selected from at least one of silica sand, glass beads, steel shot and corundum.

3. The method according to claim 1, characterized in that, The mesh size of the sandblasting material is 100-300 mesh.

4. The method according to claim 1, characterized in that, The silicon-carbon source gas is selected from at least one of trichloromethylsilane, trichlorosilane, and tetrachlorosilane.

5. The method according to claim 1, characterized in that, The carrier gas is selected from hydrogen.

6. The method according to claim 1, characterized in that, The diluting gas is selected from at least one of argon, nitrogen, and helium.

7. The method according to claim 1, characterized in that, In step (3), the ratio of the flow rate of the silicon-carbon source gas to the flow rate of the carrier gas is 1:(4-20).

8. The method according to claim 1, characterized in that, The flow rate of the silicon-carbon source gas is 30 g / min to 180 g / min.

9. The method according to claim 1, characterized in that, The flow rate of the carrier gas is 50L / min-150L / min.

10. The method according to claim 1, characterized in that, The flow rate of the diluent gas is 30L / min-120L / min.

Citation Information

Patent Citations

  • 1500-1700 DEG C carbon / carbon composite material surface oxidation-resistant coating and preparation method

    CN108530109A